Analytical Nonlinear Modeling of Rail and Fastener Longitudinal Response. Issue 5 (May 2022) - Dersch, Marcus S.; Silva, Matheus Trizotto; Edwards, J. Riley; de Oliveira Lima, Arthur
Comparatively little attention has been given to the quantification of fastener demands, especially in the longitudinal direction. Research quantifying fastener demands is justified by the more than 250 FRA reportable derailments on mainlines and sidings in the United States caused by "defective or missing spikes or rail fasteners" over the last 20 years. Failed fasteners are rarely caused by loads acting from a single direction (vertical, lateral, or longitudinal); they occur from a combination of these loads. A literature review identified that though multiple models have been developed for analyzing track, they were not designed to quantify fastener demands, especially those in the longitudinal direction, and some make assumptions that could be improved on based on more recent research into the mechanics of fastening system behavior. This paper advances the mechanistic–empirical (M-E) track analysis and design approach through the development, validation, and application of a 3D nonlinear parametric track model that quantifies longitudinal fastener demands. Key research findings include: bilinear approximations, in combination with considering the interaction between vertical loads and slip, were necessary to accurately quantify fastener forces; ballast and fastener stiffness had a direct logarithmic relationship on fastener load; and for well-supported sleepers, changes in component resistance to slip produced minimal changes in fastener demands because the vertical applied load increased the required load to produce slip. Going forward, this validated model could be used to quantify fastener and track demands for additional loading and operational scenarios to further optimize component design for improved track safety and reliability.